Classification of Rheumatoid Joint Inflammation Based on Laser Imaging - Schwaighofer, Anton; Tresp, Volker; Mayer, Peter; Krause, Andreas; Beuthan, Jürgen; Rost, Helmut; Metzger, Gerhard; Müller, Gerhard A.; Scheel, Alexander K. (IEEE Transactions on Biomedical Engineering, 2003)
We describe a classification system for a novel imaging method for arthritic finger joints. Basis of this system is a laser imaging technique which is sensitive to the optical characteristics of finger joint tissue. From the laser images acquired at baseline and followup, finger joints can automatically be classified according to whether the inflammatory status has improved or worsened. To perform the classification task, various linear and kernel-based systems were implemented and their performances were compared. Based on the results presented in this paper, we conclude that the laser-based imaging permits a reliable classification of pathological finger joints, making it a sensitive method for detecting arthritic changes.